THE STUDENTS’ COMPREHENSION IN ANALYZING ENGLISH TEXT OF THE MA DARUL FURQAN NW MENGKURU GRADERS - mul muliadi (JUPE : Jurnal Pendidikan Mandala, 2019)
This research is aimed to measure the students’ compression in analyzing English text for the students of MA Darul Furqan NW Mengkuru. The students’ comprehension in analyzing English text for the tenth year students of MA Darul Furqan NW Mengkuru are in average level. It can be seen from the mean score of the students that is 31.35 in which this number belongs average level. The percentages of successes of students’ comprehension in analyzing English text for the tenth year students of MA Darul Furqan NW Mengkuru are low. After the scores were classified for the students’ comprehension in analyzing English text, the researcher found 4 students who got very high score. It means that there were 13.33% of them were categorized very high level. Furthermore, there were 4 students who got high level; it means that there were 13.33% of students who were categorized high level. There were7 students who got sufficient level; it means that there were 23.33% of students who were categorized high level, and there were 15 students who got low level; it means that there were 50% of students who were categorized low level, moreover, there were none of students who got very.